Synthesis and antibacterial activity of ionic liquids and organic salts based on penicillin g and amoxicillin hydrolysate derivatives against resistant bacteria - Ferraz, R (2020)
The preparation and characterization of ionic liquids and organic salts (OSILs) that contain anionic penicillin G [secoPen] and amoxicillin [seco-Amx] hydrolysate derivatives and their in vitro antibacterial activity against sensitive and resistant Escherichia coli and Staphylococcus aureus strains is reported. Eleven hydrolyzed ß-lactam-OSILs were obtained after precipitation in moderate-to-high yields via the neutralization of the basic ammonia buffer of antibiotics with different cation hydroxide salts. The obtained minimum inhibitory concentration (MIC) data of the prepared compounds showed a relative decrease of the inhibitory concentrations (RDIC) in the order of 100 in the case of [C2OHMIM][seco-Pen] against sensitive S. aureus ATCC25923 and, most strikingly, higher than 1000 with [C16Pyr][seco-Amx] against methicillin-resistant Staphylococcus aureus (MRSA) ATCC 43300. These outstanding in vitro results showcase that a straightforward transformation of standard antibiotics into hydrolyzed organic salts can dramatically change the pharmaceutical activity of a drug, including giving rise to potent formulations of antibiotics against deadly bacteria strains.